Climate conscious design of light structures for improving the liveability of urban environments - Rossella Siani; Francesco De Luca (Techne)
A climate-neutral urban environment can benefit from light structures that provide relief from urban overheating in warm seasons, reduce surface temperatures, and lower energy needs and carbon emissions while sequestering carbon through bio-based materials. This research introduces a temporary architectural system to enhance thermal comfort year-round in urban spaces. Combining parametric design with computational morphogenesis, the system optimises shading and airflow to reduce summer heat stress while retaining solar radiation in winter. The modular structure integrates visually with its surroundings without obstructing views. Climate simulations and a 1:30 scale prototype confirm its feasibility, offering a sustainable, adaptable solution for diverse urban climates and contributing to climate-responsive design.